Housing valuation, wealth perception and homeowner's portfolio composition - Camões, F.; Vale, S. (Journal of Family and Economic Issues, 2018)
This study explores the link between wealth perception from an appreciation of the residential property price and homeowners’ preference toward asset categories pooled by risk. Household survey data for Portugal were used to build shares of low, medium, and high risk assets representing fractions of household’s total wealth. Data showed incomplete household portfolios along with housing capturing the largest share of households’ wealth, in line with the literature on composition puzzles. The findings indicate robust empirical evidence that the rate of housing valuation is an indicator of households’ wealth perception. When the housing price appreciates with respect to its initial cost, households suffer an endowment effect and tend to increase diversity in their portfolio, expanding the holdings of safe deposits as they raise the share of high risk assets.